Biliary tract reconstruction with or without T-tube in orthotopic liver transplantation: a systematic review and meta-analysis. (April 2015) - Sun, Ning; Zhang, Jialin; Li, Xin; Zhang, Chengshuo; Zhou, Xiangyu; Zhang, Chong
<x xml:space="preserve">Abstract</x> Introduction: At present whether to use T-tube or not during orthotopic liver transplantation (OLT) in biliary tract reconstruction still remains controversial. Most transplant centers choose not to use T-tube because the T-tube can increase the incidence of cholangitis, but some centers still use T-tube because the T-tube can decrease the incidence of anastomotic strictures. Aim: The purpose of this study is to compare biliary complications after biliary tract reconstruction with or without T-tube in OLT. Methods: systematic review and meta-analysis of a collection of 15 studies (six randomized control trails (RCTs) and nine comparative studies) to compare biliary complications after biliary tract reconstruction with or without T-tube in OLT. Results: The data showed that the biliary tract reconstruction with T-tube and without T-tube had equivalent outcomes for overall biliary complications (six RCTs p = 0.76; odd ratio [OR] = 1.19; 95% CI: 0.40, 3.58; all studies p = 0.14; OR = 1.50; 95% CI: 0.88, 2.57), bile leaks (six RCTs p = 0.61; OR = 0.86; 95% CI: 0.49, 1.52; all studies p = 0.09; OR = 1.39; 95% CI: 0.95, 2.02), cholangitis (six RCTs p = 0.13; OR = 5.54; 95% CI: 0.62, 49.79; all studies p = 0.08; OR = 4.27; 95% CI: 0.86, 21.16), hepatic artery thrombosis (two RCTs p = 1.00; OR = 1.00; 95% CI: 0.22, 4.49; all studies p = 0.75; OR = 1.19; 95% CI: 0.41, 3.44). However, in the group with T-tube there were better outcomes for biliary strictures (six RCTs p = 0.0003; OR = 0.34; 95% CI: 0.19, 0.61; all studies p < 0.0001; OR = 0.49; 95% CI: 0.34, 0.69). Discussion: Although most organizations choose not to use T-tube in OLT, we suggest that use of T-tube in biliary tract reconstruction during OLT for the recipients who possibly have high risks of biliary stricture is useful and necessary.